The relationship between college students’ psychological resilience and autonomous fitness behavior: a moderated mediation model - Wang, Xiaoheng; Zhao, Xiang; Li, Na (Frontiers in Psychology, 2025)
ObjectiveThis paper aims to explore the influence of psychological resilience on autonomous fitness behavior among college students, as well as the mechanism of perceived social support and exercise self-efficacy in this relationship.MethodsUsing literature review, questionnaire surveys, and mathematical statistics, we conducted a survey among 985 college students, administering the Psychological Resilience Scale, Autonomous Fitness Behavior Scale, the Perceived Social Support Scale, and the Exercise Self-efficacy Scale.Results(1) College students’ psychological resilience has a direct impact on their autonomous fitness behavior and can positively predict it (β = 0.833, t = 14.680, p < 0.001); (2) Perceived social support plays a partial mediating role between psychological resilience and autonomous fitness behavior among college students, with a mediating effect value of 0.288 (t = 21.415, p < 0.001); (3) Exercise self-efficacy regulates the first half of the mediating path of “psychological resilience → perceived social support → autonomous fitness behavior” (β = 0.545, t = 14.680, p < 0.001). The interaction between psychological resilience and exercise self-efficacy affects perceived social support, which in turn indirectly affects autonomous fitness behavior. Under the regulation of this mediating model, the predictive effect of psychological resilience on autonomous fitness behavior varies significantly across different levels of self-efficacy.Conclusion(1) Psychological resilience can directly promote college students’ autonomous fitness behavior, and can promote their autonomous fitness behavior through perceived social support. Perceived social support plays a partial mediating role between psychological resilience and autonomous fitness behavior, and this mediating effect can be moderated by exercise self-efficacy. (2) Compared with high exercise self-efficacy, for college students with low exercise self-efficacy, perceived social support plays a stronger mediating role.